THEORETICAL AND EXPERIMENTAL STUDIES OF THE SPECTRAL CHARACTERISTICS OF DOPED SEMICONDUCTORS USING ZINC OXIDE AND SULFIDE - Aleksandrova, Yulia; Budanova, Natalia; Farmakovskaya, Ariadna; Okorokova, Nadezhda; Ustyuzhaninova, Galina; Zharova, Nelli; Kohlert, Victoria (Revista Inclusiones, 2019)
In this work, we studied the spectral characteristics of the energy structure of Fe2+ ions in ZnO and ZnS semiconductor materials. The spectral characteristics of semiconductors doped with iron ions were obtained by direct matrix analysis. The wavelengths of the absorption bands obtained experimentally and according to the calculations showed a good correlation. The possibility of obtaining laser radiation on these materials in the range of 1.5 – 3 microns was evaluated.